-1-m/10=1

Simple and best practice solution for -1-m/10=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-m/10=1 equation:


m in (-oo:+oo)

-(m/10)-1 = 1 // - 1

-(m/10)-1-1 = 0

-1/10*m-2 = 0 // + 2

-1/10*m = 2 // : -1/10

m = 2/(-1/10)

m = -20

m = -20

See similar equations:

| 4/2=9/x | | 6x-7(-2x+5)=65 | | 3(x+60)(x-2)=60 | | -0.75n-21=-15 | | 9√25/√50 | | 5h^2-605=0 | | 13y+x=66 | | 4v/10 | | -3(x-4)=24 | | y=0x-6 | | 2m^2+80m=0 | | X+2=2.10 | | tan(40=3/x | | 7.5-2n=-2 | | 9-8x=-4-8x | | x-3/15x6x-18/5x | | -2a=10+(-7) | | cosx+sinx=2x | | x^2-48x=-104 | | 2(6x^2+11)=0 | | 7.68=3x | | ((400-2x)/2)x | | 9u^2-162u=0 | | 3x^2-6x+21=0 | | 12x^2=22 | | 88=r-92 | | -28=-4n-4 | | (400-2x/2)x | | 2(2x+4)=2(x+2) | | (y/18)-(y/6)=(4y/3) | | 8n-4n+n+18=5(n+3) | | 43=y-93 |

Equations solver categories